2013
DOI: 10.1111/vde.12040
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of biofilm production byPseudomonas aeruginosafrom canine ears and the impact of biofilm on antimicrobial susceptibilityin vitro

Abstract: Biofilm production by otitis isolates of P. aeruginosa is common and may play a role in the pathogenesis of disease. The MICs for biofilm-embedded bacteria differ from their planktonic counterparts, potentially leading to a lack of response to treatment. If polymyxin B, gentamicin, neomycin or enrofloxacin is to be used for topical treatment of a Pseudomonas otitis, the concentration of the medication should be increased, in particular if addressing chronic otitis, because biofilms may have developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
48
4
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(64 citation statements)
references
References 29 publications
7
48
4
1
Order By: Relevance
“…For P. aeruginosa canine OE isolates ( n = 20) in our study, 95% were biofilm producers, evenly distributed between weak (30%), moderate (35%) and strong (30%) biofilm production. This contrasts with a similar study by Pye et al () in which only 40% (33/83) of P. aeruginosa canine otic isolates produced biofilms (8.4% (7/83) weak, 18.1% (15/83) moderate and 13.3% (11/83) strong). In humans, the majority (77.5%) of P. aeruginosa isolates formed weak (42.5%), moderate (27.5%) or strong (5%) biofilms (Lima et al, ).…”
Section: Discussioncontrasting
confidence: 79%
“…For P. aeruginosa canine OE isolates ( n = 20) in our study, 95% were biofilm producers, evenly distributed between weak (30%), moderate (35%) and strong (30%) biofilm production. This contrasts with a similar study by Pye et al () in which only 40% (33/83) of P. aeruginosa canine otic isolates produced biofilms (8.4% (7/83) weak, 18.1% (15/83) moderate and 13.3% (11/83) strong). In humans, the majority (77.5%) of P. aeruginosa isolates formed weak (42.5%), moderate (27.5%) or strong (5%) biofilms (Lima et al, ).…”
Section: Discussioncontrasting
confidence: 79%
“…Biofilms are known to develop within the middle ear of children (Bakaletz 2007) and several authors (Pye and others 2013) have suggested the same process occurs in the middle ears of dogs. A wide range of microbes are capable of forming biofilms, including many of the most common otic pathogens.…”
Section: Perpetuating Factorsmentioning
confidence: 99%
“…Biofilm formation and susceptibility testing was carried out as documented in a previous study . Following microtitre plate incubation and biofilm formation, the optical density of each well was measured at 570 nm (OD 570 ).…”
Section: Methodsmentioning
confidence: 54%
“…Thirty‐one multidrug‐resistant P. aeruginosa isolates recovered from the ears of dogs with otitis externa that were previously demonstrated to produce biofilm in vitro were studied . Each individual isolate was obtained from a separate dog.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation